TAJASSUS IN THE QUR'AN: IMPLEMENTATION, LAWS, AND DEVIATIONS - Amri, Yaser (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2023)
The Qur'an does not discuss tajassus specifically. It is proven by the lack of the word tajassus, especially when it is based on the meaning of spying. Implicitly, the value of tajassus is found in several stories and verses collectively, which leads to fault-finding or vigilance. A particular verse about tajassus with a negative connotation is Surah al-á¸¤ujurÄt12. An example of tajassus with a positive sense is Surah YÅ«suf 87. The research in this paper is classified as literature research with a qualitative approach. The methodology used is a descriptive analysis study. The results of this study are two: First, there are two types of tajassus: tajassus in the positive sense and negative tajassus. Positive tajassus is the importance of the existence of intelligence for the state. Negative tajassus is prejudice or finding fault in others. Second, the implementation of tajassus is similar between classical and modern times, the only difference being the use of technology at different times. The tajassus deviation in this study occurred when UmÄr entered the house without permission. While in modern tajassus is the use of wiretapping devices outside the authority of the perpetrators.